Integrated GIS tool for investigating the relationship of road characteristics with road traffic accidents - Nur Fatma Fadilah Yaacob,; Noradila Rusli,; Sharifah Norashikin Bohari,; Muhamad Razuhanafi Mat Yazid,; Muhammad Das, Amsori (Penerbit Universiti Kebangsaan Malaysia, 2020)
Road accidents pose a serious economic and social problems given that the number of fatal accidents continue to rise at the national and international levels. This study investigates the relationship between three road parameters, namely number of lanes, level of service (LOS), and slope, with road accidents. The data for road accidents were obtained from the Police Department - Contingent Headquarters (IPK) Alor Setar, Kedah, the data for roads, namely number of lanes and traffic volume, were obtained from Public Works Department (JKR), while the TanDEM-X Image was provided by the licensed holder. The ArcGIS software 10.5 was used to process the data; this is followed by performing the regression and kernel density estimation to determine the relationship between the parameters with accident cases. The majority of road accidents in Kedah occurred on two-lane roads. LOS is negatively correlated with road accidents, which indicates that less accidents occurred with higher level of flow. Slope is negatively correlated with road accidents, indicating that a smaller number of accidents occurred on roads with higher slope values. Alor Setar and Sungai Petani have been identified as road traffic accident hotspots for the period from 2013 to 2015. In summary, the findings of this study provide the relevant authority such as the Traffic Police with the critical information required to make a better decision when formulating strategies to reduce road traffic accidents.